2022
DOI: 10.3389/fcvm.2022.872446
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COPD or Asthma on the Risk of Atrial Fibrillation: A Systematic Review and Meta-Analysis

Abstract: Background:Respiratory diseases related to chronic pulmonary ventilation dysfunction are mainly composed of chronic obstructive pulmonary disease (COPD) and asthma. Our meta-analysis aimed to illustrate the association of COPD or asthma with risk of atrial fibrillation (AF).MethodsWe systematically searched the databases of the PubMed, Embase, and Cochrane library until December 2021 for studies focusing on the relationship between COPD or asthma and AF risk. Due to the potential heterogeneity across studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Asthma and atrial brillation have in ammatory pathophysiological mechanisms in common which may help to explain this association [23]. Based on the random-effects model, investigators suggested that asthma (RR = 1.08, 95% CI: 1.04-1.12) was remarkably correlated with an elevated risk of atrial brillation, by utilizing meta-analysis included 14 studies [24]. In a large multiethnic cohort study (comprising 17,514 people) with 12.9 years follow-up, investigators have reported that patients with persistent, not intermittent, asthma had a higher risk of atrial brillation (hazard ratio, 1.49; 95% CI, 1.03-2.14) in comparison with those with non-asthmatic asthma [25].…”
Section: Discussionmentioning
confidence: 99%
“…Asthma and atrial brillation have in ammatory pathophysiological mechanisms in common which may help to explain this association [23]. Based on the random-effects model, investigators suggested that asthma (RR = 1.08, 95% CI: 1.04-1.12) was remarkably correlated with an elevated risk of atrial brillation, by utilizing meta-analysis included 14 studies [24]. In a large multiethnic cohort study (comprising 17,514 people) with 12.9 years follow-up, investigators have reported that patients with persistent, not intermittent, asthma had a higher risk of atrial brillation (hazard ratio, 1.49; 95% CI, 1.03-2.14) in comparison with those with non-asthmatic asthma [25].…”
Section: Discussionmentioning
confidence: 99%
“…The first, which included 14 studies, examined the risk for developing AF in patients with COPD and asthma. The results showed that COPD (OR = 1.74; 95% CI: 1.70–1.79) and asthma (OR = 1.08; 95% CI: 1.04–1.12) were significantly associated with an increased risk of AF [ 12 ]. Twenty-one studies were selected for the second meta-analysis.…”
Section: Factors Associated With Developing Atrial Fibrillation In Co...mentioning
confidence: 99%
“…Twenty-one studies were selected for the second meta-analysis. The presence of COPD was significantly associated with the risk for developing AF (OR = 1.99; 95% CI: 1.46–2.70), ventricular arrhythmias (OR = 2.01; 95% CI: 1.42–2.85), and sudden cardiac death (OR = 1.68; 95% CI: 1.28–2.21) [ 12 ]. A number of pathogenetic features of COPD are currently known to contribute to the development and progression of the disease.…”
Section: Factors Associated With Developing Atrial Fibrillation In Co...mentioning
confidence: 99%